Front Cover: Identification of Changing Ribosome Protein Compositions using Mass Spectrometry. Issue 20 (23rd October 2018) - Samir, Parimal; Browne, Christopher M.; Rahul; Sun, Ming; Shen, Bingxin; Li, Wen; Frank, Joachim; Link, Andrew J.
Abstract : DOI:10.1002/pmic.201800217 Eukaryotic cells contain different types of ribosomes that differ in their protein and RNA composition. The ribosome filter hypothesis predicts that the different ribosomes will translate specific mRNAs with differing efficiency. This allows the cells to fine tune the gene expression to different environmental conditions. It is an example of ribosomes acting as regulatory elements in translational control. Further details can be found in article number1800217 by Samir et al.